Donatism in North Africa (An Analytical Study) - Kernab, Abderaouf (Journal of Ecohumanism, 2026)
This research examines Donatism as one of the most important Christian sects that emerged in North Africa during the Roman period. It seeks to analyze the circumstances of its emergence, the reasons for its appearance, its beliefs, and its areas of spread, while shedding light on the personality of its founder, Donatus, and his role in consolidating this movement. The study concludes that Donatism was not merely a doctrinal religious schism, but rather represented a religious-political protest movement that expressed the rejection by the local population of the alliance between the Catholic Church and Roman authority, as well as their aspiration for social justice and symbolic independence. The research also highlights that the spread of Donatism was closely linked to deteriorating social and economic conditions, which made it the dominant Christian sect in vast areas of North Africa. The study concludes by emphasizing the importance of studying Donatism to understand the nature of the interaction between religion and politics in the ancient history of the region.